The Processing of Catfish into Nuggets as a Business Opportunity during the Covid-19 Pandemic - Isna Yunita Sari; Gideon Setyo B; Abiyu Ibnuyasa; Yulia Oktaviani; Chiara Baptista V; Amirah Shinta Permatasari (MITRA: Jurnal Pemberdayaan Masyarakat, 2021)
Catfish is a food ingredient that is readily widespread and can easily be cultivated, although the community might have relatively limited space. Catfish may also provide several business opportunities for the community amidst the covid-19 pandemic. One potentially profitable business idea is to process catfish into nuggets because nuggets are popular among both children and adults alike. Nuggets can also be used as a practical substitute for side dishes. This activity aims to provide training on how to process catfish into nuggets for the women from PKK (Family Welfare Development/Pembinaan Kesejahteraan Keluarga) and cadre programs in Lidah Wetan Gang VI, Lakarsantri, Surabaya. The program was held in PPT CERIA RT 3 RW 3, Lidah Wetan Gang VI, Lakarsantri, Surabaya. Before the training, all the necessary permits and information were obtained to ensure the program's success. The training activity shows how the catfish nuggets have a shape and texture of typical nuggets with their taste like chicken nuggets. However, what makes the catfish nuggets unique is that they still retain a slight distinctive catfish taste. It is expected that this activity will benefit the community, especially those interested in the catfish processing business.